Numerical Solutions of Maxwell’s Equations to Calculate Waves Propagation in Dielectric Material using Finite Difference Time Domain (FDTD) Technique - Farhat, Sedig (The Libyan Journal of Science, 2024)
This paper presents the numerical solutions of Maxwell’s time dependent curl equations by using finite difference time domain (FDTD) technique for simulating the electromagnetic waves propagation in a dielectric medium designed in different shapes in two dimensional system. The waves propagated in the dielectric slab, which can be studied to show that for the example, a dielectric medium can use to guide the waves in a material. The results of the calculations indicated that the performance of a dielectric slab model acted as a guide of the signals. The impact of a dielectric slab orientation variation can be studied. The results demonstrated that each change in the shape structure of a dielectric could result into the different distributions, as an example two different distributions generated when the dielectric slabs oriented in the x-direction compared with y-direction. Moreover, the propagations of the waves can be studied when varying the phase. The first simulation the dielectric slabs placed in free space and the second the dielectric slab placed between two parallel strips made of the perfect electric conductors (PECs). The result of the first simulation demonstrated that the signal updated on the dielectric as well as free space while the result of the second simulation, the signal only updated in the dielectric slab between the strips. In one dimensional (1-D) as an example of the propagation of electromagnetic wave in a dielectric constant compared with PEC. The results have shown that it is possible to study two different types of materials in a one simulation. Therefore, the results obtained clearly demonstrated that electromagnetic wave completely reflected back into a domain when the pulse is striking with the PEC while in a region of dielectric, the pulse propagated in a dielectric constant and the other parts reflected back into a domain.